Predlog racionalnega presejanja osteoporoze v osnovnem zdravstvu - Hren, Rok (Zdravniški vestnik, 2002)
Background. Early identification of postmenopausal women with osteoporosis by means of bone mineral density (BMD) measurement is a prerequisite for reducingthe incidence of osteoporotic fractures. Primary care physicians have a leading role in referring such patients, however, given the cost of the BMD measurement, efficient screening criteria remain to be determined. Currently available criteria (e. g., SCORE, ORAI) are very broad with low specificity. Objective of our study is to assess simple decision rules that could enhance identifying patients with high risk of fracture while concurrently minimizing number of unnecessary measurements. Methods. In the study, 357 primary care physicians (GPs and gynecologists) referred their patients to BMD measurementsbased on the following decision rules women (i) should be postmenopausal for at least 5 years, (ii) should have body mass index (BMI) less than 26 kg/m2 and (iii) should have never been diagnosed with osteoporosis. BMD of lumbarspine and/ or hip was measured by dual-energy x-rayabsorptiometry (DXA) in 5 centers using Hologic (Hologic Corp., Bedford, MA) or Lunar (Lunar Corp., Madisom, WI) densitometers. Results of BMD measurements were expressed in terms of the T-score and were forwarded to the primary care physicians. Results. 2339 postmenopausal women participated in the study; by the end of the study, 327 physicians (92%) reported results on 2196 women (94%). 1332 women of 2196 (61%) were identified as osteoporotic, 637 (29%) as osteopenic, and 227 (10%) had normal BMD. Approximately 30% of patients with osteoporosis suffered from previous low-trauma fracture. Among all women, the prevalence of osteoporosis was 34% for ages less than 55 years,50% for ages 55-59 years, and 69% for ages above 60 years. The number ofDXA measurements needed to detect one osteoporotic patient among women olderthan 60 years and with BMI < 24.5 kg/m2 was 1.32. (Abstract truncated at 2000 characters).
Keywords: Age factors; Body mass index; Bone density; Diagnosis; diagnostika; Epidemiology; Kost, gostota; Osteoporosis; Osteoporoza; Pomenopavza; Postmenopause; Prevalenca; Prevalence; preventivna medicina; Risk assessment; Starostni faktorji; Telesna masa, indeks; Tveganje, ocenjevanje